2017
DOI: 10.5578/fmbd.53893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin On the Genotoxicity Induced By Alkylating Agents

Abstract: DNA damage due to genotoxic stress is an important type of stress which organisms are exposed during the their life. The direct-acting alkylating agent methyl methanesulfonate (MMS), is covalently linked to DNA and cause DNA damage, creating an indirect effect of the alkylating agent cyclophosphamide (CP) cause to DNA damage by changing the function of cellular proteins. In this study, the effects of curcumin on MMS and CP treated mice DNA damage, total antioxidant capacity, total oxidant capacity (oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…İşitez and Ciğerci shown that dietary curcumin reduces DNA damage, number of micronuclei and oxidative stress when exposed to alkylating agents. Their findings suggest that dietary curcumin shows protective antigenotoxic effects against alkylating agents due to its phenolic component which plays important role against DNA damage [38] . Various in vitro and in vivo studies outline beneficial effects of curcumin in prevention and treatment of different cancers [10] .…”
Section: Fig 1: Genotoxicity Biomarkers Of Cisplatin Group Scored In ...mentioning
confidence: 99%
“…İşitez and Ciğerci shown that dietary curcumin reduces DNA damage, number of micronuclei and oxidative stress when exposed to alkylating agents. Their findings suggest that dietary curcumin shows protective antigenotoxic effects against alkylating agents due to its phenolic component which plays important role against DNA damage [38] . Various in vitro and in vivo studies outline beneficial effects of curcumin in prevention and treatment of different cancers [10] .…”
Section: Fig 1: Genotoxicity Biomarkers Of Cisplatin Group Scored In ...mentioning
confidence: 99%